Analysis of the Current Status of Public Education from the Perspective of Education Experts - Mesbahian, Azam; AfzalKhani, Maryam; Khanzadi, Khadijeh (Assessment and Practice in Educational Sciences, 2025)
The main objective of this study was to analyze the current status of public education from the perspective of education experts. The research employed a quantitative descriptive survey method. The statistical population included all teachers and school principals in the Department of Education of Semnan Province during the 2024–2025 academic year. Using Cochran’s formula, a sample size of 357 individuals was determined. The sampling method was stratified random sampling proportional to the educational districts. The data collection instrument was a researcher-made questionnaire developed based on components extracted from the qualitative phase of the study. After the confirmation of content validity by experts, the reliability of the instrument was calculated using Cronbach’s alpha. For data analysis, the t-test and the SPSS (version 27) and AMOS (version 24) software were utilized. The results revealed that the component “active and creative participation of learners” had a positive and significant effect on the exogenous variable (β = 0.24, p < 0.001). The path “reflection and continuous improvement” also showed a positive and significant effect (β = 0.21, p < 0.001). The construct “stable emotional, cultural, and professional foundations” had a significant and positive impact on the outcome variable (β = 0.15, p = 0.028). On the other hand, the paths related to “21st-century skill development and media literacy” (β = 0.13, p = 0.058), “systemic and flexible learning” (β = 0.08, p = 0.106), “multilayered connection with society and the world” (β = 0.07, p = 0.161), and “training transformative teachers and principals” (β = 0.06, p = 0.228) were not statistically significant and had no meaningful effect on the current state of public education. The coefficient of determination (R²) for public education was found to be 0.70, indicating that approximately 70% of the variance in the dependent variable (current status) was explained by the identified components.